Association of Lower Exposure Risk With Paucisymptomatic/Asymptomatic Infection, Less Severe Disease, and Unrecognized Ebola Virus Disease: A Seroepidemiological Study. (7th March 2022) - Kelly, J Daniel; Frankfurter, Raphael G; Tavs, Jacqueline M; Barrie, Mohamed Bailor; McGinnis, Timothy; Kamara, Mohamed; Freeman, Adams; Quiwah, Komba; Davidson, Michelle C; Dighero-Kemp, Bonnie; Gichini, Harrison; Elliott, Elizabeth; et al.
Abstract: Background: It remains unclear if there is a dose-dependent relationship between exposure risk to Ebola virus (EBOV) and severity of illness. Methods: From September 2016 to July 2017, we conducted a cross-sectional, community-based study of Ebola virus disease (EVD) cases and household contacts of several transmission chains in Kono District, Sierra Leone. We analyzed 154 quarantined households, comprising both reported EVD cases and their close contacts. We used epidemiological surveys and blood samples to define severity of illness as no infection, pauci-/asymptomatic infection, unrecognized EVD, reported EVD cases who survived, or reported EVD decedents. We determine seropositivity with the Filovirus Animal Nonclinical Group EBOV glycoprotein immunoglobulin G antibody test. We defined levels of exposure risk from 8 questions and considered contact with body fluid as maximum exposure risk. Results: Our analysis included 76 reported EVD cases (both decedents and survivors) and 421 close contacts. Among these contacts, 40 were seropositive (22 paucisymptomatic and 18 unrecognized EVD), accounting for 34% of the total 116 EBOV infections. Higher exposure risks were associated with having had EBOV infection (maximum risk: adjusted odds ratio [AOR], 12.1 [95% confidence interval CI, 5.8–25.4; trend test: P < .001) and more severe illness (maximum risk: AOR, 25.2 [95% CI, 6.2–102.4]; trend test: P < .001). Conclusions: This community-based study of EVD cases and contacts provides epidemiological evidence of a dose-dependent relationship between exposure risk and severity of illness, which may partially explain why pauci-/asymptomatic EBOV infection, less severe disease, and unrecognized EVD occurs. Abstract : This community-based study of Ebola virus disease (EVD) cases and contacts provides epidemiological evidence of a dose-dependent relationship between exposure risk and severity of illness, which may partially explain why pauci-/asymptomatic Ebola virus infection, less severe disease, and unrecognized EVD occurs.